Pengaruh Latihan Speed Agility dan Ball Feeling Terhadap Kemampuan Teknik Dribbling Futsal Siswa MAN 2 Bone - Andi Muh Sulihin; Andi Mutmainna; Rahmat Ilahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of speed agility and ball feeling training on dribbling technique ability in futsal among students of MAN 2 Bone. The study employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The research sample consisted of 16 students participating in the futsal extracurricular program at MAN 2 Bone, selected using a total sampling technique. The research instrument was a futsal dribbling test. Data were analyzed using descriptive statistics and hypothesis testing. The results showed that speed agility and ball feeling training had a significant effect on improving students’ futsal dribbling technique. Therefore, both training methods are effective alternatives for training programs to enhance basic futsal dribbling skills.